Hyperalgesia, synovitis and multiple biomarkers of inflammation are suppressed by interleukin 1 inhibition in a novel animal model of gouty arthritis. Issue 10 (14th June 2009) - Torres, R; Macdonald, L; Croll, S D; Reinhardt, J; Dore, A; Stevens, S; Hylton, D M; Rudge, J S; Liu-Bryan, R; Terkeltaub, R A; Yancopoulos, G D; Murphy, A J
Abstract : Background: Monosodium urate (MSU) and calcium pyrophosphate dihydrate (CPPD) crystal-induced interleukin 1 β (IL1β) release contributes to inflammation in subcutaneous air pouch and peritoneal models of acute gout and pseudogout. However, consequences of IL1 inhibition have not been explored in more clinically relevant models of crystal-induced arthritis. Objective: To develop a novel mouse model of acute gouty ankle arthritis and use it to assess the effects of genetic deletion of IL1 receptor type (IL1R1) and of exogenous mIL1 Trap (a high-affinity blocker of mouse IL1α and IL1β) on pain, synovitis and systemic inflammatory biomarkers. Methods: MSU crystals were injected into the mouse ankle joint and pain and ankle swelling were measured over 4 days. The effects of IL1 inhibition were determined in this model, and in the comparator models of crystal-induced peritonitis and subcutaneous air pouch inflammation. Results: Both IL1R1-null mice and mice pretreated with mIL1 Trap showed reduced neutrophil influx in MSU and CPPD crystal-induced peritonitis and air pouch models (p<0.05). In the ankle joint model, both IL1R1 knockout mice and pretreatment with mIL1 Trap were associated with significant reductions in MSU crystal-induced elevations in hyperalgesia, inflammation, serum amyloid A and the levels of multiple inflammatory cytokines and chemokines (p<0.05). Additionally, it was found that administration of mIL1 Trap after MSU crystal injection reduced established hyperalgesia and ankle swelling. Conclusions: IL1 inhibition both prevented and relieved pain and ankle joint inflammation in response to intra-articular MSU crystals in mice. Results suggested that IL1 Trap has the potential to both prevent and treat gouty arthritis.